Relativistic theory of the asymmetric field - Valenzuela, Mississippi (2022)
In this paper, we have given a presentation of the relativistic theory of asymmetric field. It is our aim to present a theory of gravitation and electomagnetism by a generalization of the concepts and mathematical methods of the general relativity. We look for the formally most simple expression for the law of gravitation in the absence of an electromagnetic field, and then the most natural generalization of this law. This theory contain  Maxwell's theory in the Lambda transformation.